1994
DOI: 10.1159/000244105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Four Tests of Bacterial Infection in the Neonate

Abstract: In a prospective study, the diagnostic value of C3d serum levels was compared with that of neutropenia, hyperfibrinogenemia and raised CRP in generalized neonatal bacterial infections. Serum C3d was evaluated using a counter-immunoelectrophoresis technique following a step of removal of C3 split products. Twelve patients with septicemia, 8 patients with highly probable infection and 134 normal controls were included in the study. The sensitivities for neutropenia, hyperfibrinogenemia, raised CRP and positive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The values for sensitivity and specificity in the literature vary widely, since there are significant differences in definitions used to count total neutrophils and sub-fractions; with sensitivity varying from 17 to 100% and specificity from 31 to 100%. 7,[17][18][19] The elevated negative predictive value of the WBC has been considered a valuable attribute, allowing clinicians greater confidence when ruling out a suspicion of late neonatal sepsis. 20 found that, during episodes of late sepsis, using sequential samples increased sensitivity from 61.5 to 84.4%…”
Section: Discussionmentioning
confidence: 99%
“…The values for sensitivity and specificity in the literature vary widely, since there are significant differences in definitions used to count total neutrophils and sub-fractions; with sensitivity varying from 17 to 100% and specificity from 31 to 100%. 7,[17][18][19] The elevated negative predictive value of the WBC has been considered a valuable attribute, allowing clinicians greater confidence when ruling out a suspicion of late neonatal sepsis. 20 found that, during episodes of late sepsis, using sequential samples increased sensitivity from 61.5 to 84.4%…”
Section: Discussionmentioning
confidence: 99%
“…Equally difficult is the exclusion of infection in infants with suspected sepsis, as continuation of broad-spectrum antibiotics for presumptive bacterial infection frequently leads to unnecessary treatment and also the possibility of emergence of multiresistant organisms. In the past decade, many investigators, including our own investigating team, have used various hematologic and biochemical markers, and cytokines such as immature/total neutrophil ratio (3,4), CRP (4 -8), procalcitonin (8 -10), TNF-␣ (5, 11), IL-1␤ (5), soluble IL-1ra (12), IL-2 receptor (13), IL-6 (5, 12), IL-8 (7,14), , and markers of complementactivation (16,17) as indicators for early or confirmation of diagnosis of neonatal infection. We have previously demonstrated that the combination of IL-6 and serial CRP measurements gave a reasonably high sensitivity and specificity for diagnosing late-onset nosocomial infection (5).…”
mentioning
confidence: 99%
“…In prematures, the volume of blood sent for culture may be lower than needed to detect the organism responsible for sepsis [16]. If the obligatory blood culture did not show growth, additional laboratory and clinical signs [17] predictive for infection [8][9][10][11] were required for "clinical sepsis." Fifty-four percent of NIs in our VLBW infants were such episodes, but only one third were culture proven.…”
Section: Discussionmentioning
confidence: 99%
“…2) CONS are isolated from blood culture/intravascular access device AND the neonate has any of the following: fever/hypothermia, apnea/bradycardia, tachycardia, time of recapillarisation > 2 s or otherwise unexplained metabolic acidosis AND at least one of the following laboratory signs: (C-reactive-protein CRP) > 2.0 mg/dl, immature/total neutrophil ratio > 0.2, leukocytopenia < 5,000/µl or thrombocytopenia < 100,000/µl. For "clinical sepsis," no organism is detected in blood culture but one of the following is present: fever/ hypothermia, apnea/bradycardia, tachycardia, time of recapillarization > 2 s or otherwise unexplained metabolic acidosis AND physician institutes appropriate antimicrobial therapy for sepsis [8][9][10][11]. "Radiographic pneumonia": radiologic examination of chest shows infiltrate, opacification, fluid in lobar fissures/pleura AND any of the following: purulent tracheal secretions, organism isolated from blood culture, isolation of pathogen in respiratory secretions, detection of pathogen antigen in respiratory secretions, CRP > 2.0 mg/dl, or immature/total neutrophil ratio > 0.2.…”
Section: Cultures Antibiotics and Surveillancementioning
confidence: 99%